Biological basis of radiation protection needs rejuvenation. (3rd October 2017) - Paunesku, Tatjana; Haley, Benjamin; Brooks, Antone; Woloschak, Gayle E.
Abstract: Purpose: Human beings encounter radiation in many different situations – from proximity to radioactive waste sites to participation in medical procedures using X-rays etc. Limits for radiation exposures are legally regulated; however, current radiation protection policy does not explicitly acknowledge that biological, cellular and molecular effects of low doses and low dose rates of radiation differ from effects induced by medium and high dose radiation exposures. Recent technical developments in biology and medicine, from single cell techniques to big data computational research, have enabled new approaches for study of biology of low doses of radiation. Results of the work done so far support the idea that low doses of radiation have effects that differ from those associated with high dose exposures; this work, however, is far from sufficient for the development of a new theoretical framework needed for the understanding of low dose radiation exposures. Conclusions: Mechanistic understanding of radiation effects at low doses is necessary in order to develop better radiation protection policy.